Temporalities of mental distress: digital immediacy and the meaning of 'crisis' in online support. (10th October 2019) - Tucker, Ian M.; Lavis, Anna
Abstract: The Internet is increasingly used to seek support by those suffering with mental distress (Bauman, S. and Rivers, I. Mental Health and the Digital Age . Basingstoke: Palgrave Macmillan; 2015). Drawing on research on a major online peer support forum, we analyse discussions around acute distress, self‐harm and suicide. The paper argues that new temporalities of mental health 'crisis' are emerging through the intersection of the immediacy of online support, the chronicity of underlying distress and the punctuated nature of professional support. Online support adds a layer of temporal immediacy that does not traditionally feature in other forms of support (e.g. professional in‐person services). This shifts the meaning of a mental health 'crisis' from acute to processual, and can lead to definitions of 'crisis' being used when not desired nor necessarily accurate. By attending to the layering of temporalities at the intersections of professional in‐person, and online support, we demonstrate how parameters of crisis support are set – by whom, for whom and in relation to whose bodies. This has implications for professional clinical practice internationally in relation to the increased digitisation of support and the meanings of 'crisis' that emerge.